Pre-operative hemoglobin level: Correlation with hemoperitoneum in ectopic pregnancy - Gurung, Geeta; Rana, Ashma (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Aim: To find out the incidence and correlation of preoperative hemoglobin level (Hb %) with hemoperitoneum in cases of ectopic pregnancy (EP). Methods: This was a prospective study carried out in Tribhuvan University Teaching Hospital (TUTH), Nepal during the period of 5 years; 15 April 2002-14 April 2007 (Baisakh 2059 - Chaitra 2063). All the cases of hemoperitoneum from rupture of EP confirmed at laparotomy were analyzed. Unruptured ectopic EP undergoing medical management or ruptured organized EP forming tubo-ovarian mass and ruptured rudimentary horn pregnancy without hemoperitoneum were all excluded. Datas were collected from patient's interview, reviewing the operation record and record file. Result: Of the total 167 EP constituting 0.963 % of all deliveries, managed during the five years period, 150 (90%) cases with hemoperitoneum were analyzed. Further excluding five cases not mentioning the amount of hemoperitoneum 145 [ < 1500ml (98) or >1500ml ->3000ml (47)] was categorized to have different degrees of anaemia was ascertained in 90 (62.1%): Severe (13), moderate (55) and mild (22). Results depicted a negative (inverse) correlation between pre operative Hb level and hemoperitoneum. Conclusion: In conclusion there is negative (inverse) correlation between pre-operative Hb percentage and hemoperitoneum which is statistically significant. Keywords: Ruptured ectopic, hemoperitoneum, hemoglobin level doi:10.3126/njog.v2i1.1475 N. J. Obstet. Gynaecol Vol. 2, No. 1, p. 39 - 43 May -June 2007